Physical Properties, Pasting Characteristics, and Rheological Behaviour of Paddy Varieties Suitable for Flaking - Saha, Dhritiman; Kumar TV, Arun; Sethi, Swati; Navnath, Indore (Food Science and Engineering, 2020)
A study was conducted to find the effect of moisture content on various physical properties of paddy varieties (MTU-1010 and BB-11) suitable for flaking. The range of moisture studied was 11.11% to 28.2% (d.b.) for both the paddy varieties. The bulk density of the paddy increased from 514.76 kg/m3 to 563.62 kg/m3 for the MTU-1010 variety and from 605.28 kg/m3 to 632.62 kg/m3 for the BB-11 variety, respectively, when the moisture content was increased in the experimental range. The sphericity increased from 0.386 to 0.399 for the MTU-1010 variety and from 0.448 to 0.458 for the BB-11 variety with an increase in moisture content. The true density and porosity decreased with the increase in moisture content of paddy. The other physical properties, such as test weight, surface area, arithmetic mean diameter, geometric mean diameter, and angle of repose, increased with the increase in moisture content of paddy. The static coefficient of friction of paddy increased with the increase in moisture content on different surfaces, e.g., wood, mild steel, and galvanized iron. The regression equations for all the response variables were significant at P < 0.05 with a coefficient of determination, R2 (> 0.90). The amylose content in the MTU-1010 and BB-11 varieties was found to be 30.23% and 26.32%, respectively, indicating that high amylose-containing paddy varieties are generally used for flaking paddy. Further, the pasting properties of both the paddy varieties revealed a higher pasting temperature in the paddy variety MTU-1010 than in BB-11. The rheological studies highlighted a higher storage modulus of brown rice than that of polished rice for both the paddy varieties.